ANALISIS KINERJA KEUANGAN PEMERINTAH KOTA BENGKULU DALAM MEWUJUDKAN PEMBANGUNAN EKONOMI BERKELANJUTAN - Ariska, Fitriani (Jurnal Ilmu Akuntansi, 2025)
This study aims to analyze the financial performance of the Bengkulu City Government and its relationship to sustainable economic development. The data were obtained from financial reports and statistical data of Bengkulu City for the period 2019–2023. The method used is financial ratio analysis and simple regression analysis. The results show that the effectiveness of locally-generated revenue (PAD) and the efficiency of regional spending are relatively high, although the fiscal independence ratio remains low. Sustainable economic development indicators such as the Human Development Index (HDI) and poverty rates have improved significantly. Regression analysis shows that financial performance has a significant influence on sustainable economic development in Bengkulu City. This study recommends improving fiscal independence and increasing capital expenditure allocation to support inclusive and sustainable economic growth.